PENERAPAN PENDEKATAN SAINTIFIK TERHADAP KEMAMPUAN KONEKSI MATEMATIS SISWA SMP - Nurainah Nurainah; Luvy Sylviana Zanthy (Departement of Mathematics Education, 2019)
This study aims to determine the effect of competitive approaches to students' mathematical connection skills in one of the junior high schools in the city of Cimahi. The method of this research is qualitative descriptive. The subjects in this study were class VIII students in one junior high school in the city of Cimahi as many as 26 students, this study used a class action approach (PTK) with data collection techniques carried out namely tests and non-tests. Tests are questions that are in accordance with mathematical connection skills with 4 ability indicators and non-tests are interviews with students with high, medium and low abilities. The results of learning research using a scientific approach by performing pretest and posttest can affect the mathematical connection ability of junior high school students with an average percentage of 83%.